Thomas M. Patterson, The Charter and Ordinances of the City of Denver, as Adopted Since the Incorporation of the City and Its Organization, November, 1861, to the First Day of February, A.D., 1875, Revised and Amended, Together with an Act of the Legislature of the Territory of Colorado, in Relation to Municipal Corporations Page 135 - (:unkn) unknown (General Publisher, 1875)
Prohibited the keeping in a place of business or elsewhere within Denver, any gun powder or gun cotton exceeding twenty-five pounds at one time. The same shall be lept in tin or copper canisters or cases not exceeding five pounds. Violators fined not less than ten nor exceeding one hundred dollars.
--
Keywords: GUN POWDER STORAGE